2015
DOI: 10.1017/s0014479715000253
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Three Years of Tillage and Poultry Manure Application on Soil and Plant Nutrient Composition, Growth and Yield of Cocoyam

Abstract: SUMMARYTillage and use of organic manure are important agronomic practices that sustain high crop and soil productivity. Hence, a three-year (2007 to 2009) study was conducted to evaluate the effect of site, tillage and poultry manure (PM) treatments on soil and plant nutrients composition, growth and yield of cocoyam (Xanthosoma sagittifolium). The study was a 2 × 5 × 5 factorial experiment with two sites (Owo – site 1 and Obasooto – site 2), five tillage methods; manual clearing (MC), manual ridging (MR), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
(20 reference statements)
3
15
1
Order By: Relevance
“…Also, the enhanced availability of nutrient supply due to biochar in addition to soil physical properties also aided the yield of cocoyam. e increase in cations in biochar-amended plots brings an improvement in soil fertility and its nutrient retention [69] especially K that is important for tuber formation of cocoyam [19]. Adekiya et al [4] reported that biochar alone because of its inert nature did not increase the yield of a short season crop like radish (Raphanus sativus L.) significantly in the first year of application; however, for cocoyam in this current study it did.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Also, the enhanced availability of nutrient supply due to biochar in addition to soil physical properties also aided the yield of cocoyam. e increase in cations in biochar-amended plots brings an improvement in soil fertility and its nutrient retention [69] especially K that is important for tuber formation of cocoyam [19]. Adekiya et al [4] reported that biochar alone because of its inert nature did not increase the yield of a short season crop like radish (Raphanus sativus L.) significantly in the first year of application; however, for cocoyam in this current study it did.…”
Section: Discussioncontrasting
confidence: 50%
“…Cocoyams are the cheapest and most handy source of carbohydrate in meals that are recommended for aged people, diabetics, convalescents, and most gastrointestinal disorder patients [19]. Moreso, Cocoyam, being a tuber crop, is sensitive to poor soil physical conditions [20] and potassium (K) in the soil [19]. Application of biochar could be a way of improving the physical and chemical soil condition and yield of cocoyam.…”
Section: Introductionmentioning
confidence: 99%
“…Application of poultry manure to crop lands as a nutrient source serves as an important means of its safe disposal (Reddy et al, 2008). Nutrients provided by poultry manure have been reported to have positive effects on crop production (Mitchell and Tu, 2005;Reddy et al, 2007;Adekiya et al, 2016). Continuous application of poultry manure will increase levels of soil nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficient between yield parameters of ginger and soil physical and chemical properties. Significant difference at p = 0.01 density would have increased greater root growth and nutrient adsorption and hence greater yield relative to the control Adekiya et al (2016). also found PM to increase the growth and yield of cocoyam.…”
mentioning
confidence: 82%